Bài 1. Nguyên hàm


Tìm a) \(\int {{{{x^2} - 3x} \over x}} dx\)                  b) \(\int {{{4{x^3} + 5x - 1} \over {{x^2}}}} dx\)c) \(\int {{{{{\left( {x + 2} \right)}^2}} \over {{x^4}}}} dx\)         ...
Tìm a) \(\int {\left( {{x^{{3 \over 4}}} + {x^{{1 \over 2}}} - 5} \right)} dx\)                                                  b) \(\int {\sqrt x \left( {\sqrt x  - 2x} \right)} \left( {x + 1} \right)dx\)c) \(\int {\left( {{x^{ - 3}} - 2{x^{ - 2}}...
Tìm hàm số \(y = f\left( x \right)\), biết rằng a) \(f\left( x \right) = 2x + 1\) và \(f\left( 1 \right) = 5\)                           b) \(f\left( x \right) = 2 - {x^2}\) và \(f\left( 2 \right) = {7 \over 3}\)c) \(f\left(...
Tìm hàm số \(y = f\left( x \right)\) nếu biết \(f'\left( x \right) = ax + {b \over {{x^2}}},f\left( { - 1} \right) = 2,f\left( 1 \right) = 4,f'\left( 1 \right) = 0\).Giải \(f\left( x \right) = {{a{x^2}} \over 2} -...
Tìm hàm số \(y = f\left( x \right)\) nếu biết \(f'\left( x \right) = {{15\sqrt x } \over {14}},f\left( 1 \right) = 4\)Giải\(f(x)={{5\sqrt {{x^3}} } \over 7}+C\)Vì \(f\left( 1 \right) = 4\) nên \({5 \over 7} + C = 4...
Tìm nguyên hàm của các hàm số sau: a) \(y = 1 - x\)                                 b) \(y = 2 + {x^2}\)                              c) \(y = {x^3}...
Tìm nguyên hàm của các hàm số sau: a) \(y = \left( {x + 2} \right)\left( {x - 3} \right)\)   b) \(y = \left( {{x^2} - 3x} \right)\left( {x + 1} \right)\)c) \(y = {\left( {x - 3} \right)^3}\)                                                  d)...